Applying for Settled Status: Ambivalent and reluctant compliance of EU citizens in post-Brexit Scotland. Issue 3 (August 2020) - Botterill, Kate; Bogacki, Mariusz; Burrell, Kathy; Hörschelmann, Kathrin
Abstract : This article contributes to scholarship concerning the effects of the UK Referendum on EU membership and Brexit on EU citizen rights in the UK (Botterill, McCollum and Tyrrell, 2018 ; Burrell and Schweyher, 2019 ; Gawlewicz and Sotkasiira, 2019 ; Huber, 2019 ). The paper focuses on applications for, and meanings of, 'settled status' among Polish nationals living in urban and rural Scotland. In particular we argue that the 'simple' act of application produces diverse responses among Polish nationals, characterised by ambivalent and reluctant compliance, with longer term implications for ontological security and sustainable communities. In the paper we present empirical data from the perspectives of three differently positioned individuals to illustrate the heterogenous experience of Polish nationals in Scotland and to demonstrate how pre-existing vulnerabilities and conditions are compounded by the EU settlement scheme. First, we highlight a view of citizenship as 'social contract' through the vignette of Marek who expresses ambivalence about Brexit and for whom the welfare system serves both as a safety net and a space of the undeserving. Second, we reflect on the complex bureaucratic process of gaining citizenship for a family, through the vignette of Monika. Finally, we consider how form filling is an anxious act of validating oneself and questioning one's belonging to place with longer term effects on ontological insecurity, through the vignette of Weronika. We conclude by offering a set of recommendations for Scottish policy on intercultural communication, integration and sustainable communities that, in the context of the COVID-19 pandemic, is ever more significant.